2013
DOI: 10.1016/j.energy.2012.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of a binary geothermal power plant

Abstract: 6A model is developed for an existing organic Rankine cycle (ORC) utilizing a low temperature geothermal source. The model is implemented in Aspen Plus ® and used to simulate the performance of the existing ORC equipped with an air-cooled condensation system. The model includes all the actual characteristics of the components. The model is validated by approximately 5000 measured data in a wide range of ambient temperatures. The net power output of the system is maximized. The results suggest different optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 25 publications
0
40
1
Order By: Relevance
“…Several authors examine, in a limited sense, the effect of superheaters [2,3], recuperators [4], and both superheaters and recuperators [5][6][7][8]. Ghasemi et al show that with isobutane as a working fluid at a brine temperature of 135°C, the optimum amount of superheat increases with increasing ambient temperature [3]. Walraven et al conclude that for a brine temperature of 125°C and a condenser temperature of 25°C, recuperation is always useful [4].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several authors examine, in a limited sense, the effect of superheaters [2,3], recuperators [4], and both superheaters and recuperators [5][6][7][8]. Ghasemi et al show that with isobutane as a working fluid at a brine temperature of 135°C, the optimum amount of superheat increases with increasing ambient temperature [3]. Walraven et al conclude that for a brine temperature of 125°C and a condenser temperature of 25°C, recuperation is always useful [4].…”
Section: Introductionmentioning
confidence: 97%
“…Extensive technical literature examines these complex systems, and among this literature, the most common added complexities are a superheater and a recuperator (described in detail in Section 2). Several authors examine, in a limited sense, the effect of superheaters [2,3], recuperators [4], and both superheaters and recuperators [5][6][7][8]. Ghasemi et al show that with isobutane as a working fluid at a brine temperature of 135°C, the optimum amount of superheat increases with increasing ambient temperature [3].…”
Section: Introductionmentioning
confidence: 98%
“…They reported that, under the exergoeconomic optimization conditions, isobutane with a minimum temperature difference of 3 K at evaporation and 7 K at condensation is favorable. For an existing ORC utilizing low temperature geothermal source, with isobutane as the working fluid, a thermodynamic model is developed by Ghasemi et al [14] and validated by approximately 5000 measured data in a wide range of ambient temperatures. Zhang et al [15] examined the thermodynamic and economic performance of both subcritical and trans-critical ORC for low-temperature geothermal sources.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in the need for energy and the limited resources of fossil fuels as well as their adverse environmental effects (including global warming) have led to increased efforts to use clean energy sources. The geothermal energy has a prominent place among the renewable energies due to vast resources on the ground (Lavizeh, 2002;Saidi et al, 2005b;Ehyaei andBahadori, 2006, 2007;Ahmadi and Ehyaei, 2009;Najafi and Ghobadian, 2011;Vélez et al, 2012;Ehyaei et al, 2013;Ghasemi et al, 2013;Astolfi et al, 2014;Ehyaei, 2014;Asgari and Ehyaei, 2015;Darvish et al, 2015;Saffari et al, 2016). So far, many studies have been conducted on the use of geothermal energy.…”
Section: Introductionmentioning
confidence: 99%